Prevalence, Incidence, Prognosis, Early Stroke Risk, and Stroke-Related Prognostic Factors of Definite or Probable Transient Ischemic Attacks in China, 2013 - Jiang, Bin; Sun, Haixin; Ru, Xiaojuan; Sun, Dongling; Chen, Zhenghong; Liu, Hongmei; Li, Yichong; Zhang, Mei; Wang, Limin; Wang, Linhong; Wu, Shengping; Wang, Wenzhi (Frontiers in Neurology, 2017)
The epidemiological characteristics of transient ischaemic attacks (TIAs) in China are unclear. In 2013, we conducted a nationally representative, door-to-door epidemiological survey on TIA in China using a complex, multistage, probability sampling design. Results showed that the weighted prevalence of TIA in China was 103.3 (95% confidence interval (CI): 83.9–127.2) per 100,000 in the population, 92.4 (75.0–113.8) per 100,000 among men, and 114.7 (87.2–151.0) per 100,000 among women. The weighted incidence of TIA was 23.9 (17.8–32.0) per 100,000 in the population, 21.3 (14.3–31.5) per 100,000 among men, and 26.6 (17.0–41.7) per 100,000 among women. No difference in average prognosis was found between TIA and stroke in the population. Weighted risk of stroke among TIA patients was 9.7% (6.5%-14.3%), 11.1% (7.5%-16.1%), and 12.3% (8.4%-17.7%) at 2, 30, and 90 days, respectively. The risk of stroke was higher among male patients with a history of TIA than among female patients with a history of TIA (OR: 2.469; 95% CI: 1.172-5.201; P=0.018), and higher among TIA patients with hypertension than among TIA patients without hypertension (OR: 2.671; 1.547-4.613; P<0.001). It can be concluded that there are an estimated 1.35 million TIA patients nationwide, with 0.31 million new cases of TIA annually in China. TIA patients were not better managed prior to a stroke event. Early risk of stroke among TIA patients is high. Sex and hypertension may be stroke-associated prognostic factors among TIA patients. TIA clinics and surveillance should be integrated into the national health care system.